THE EFFECT OF DIET SHOF (SIXTEEN HOUR OF FASTING) ON TRIGLYCERIDE LEVELS IN OVERWEIGHT ADOLESCENTS - Khotimah, Khotimah; Herin Mawarti, (International Journal of Social Science, 2023)
Body weight exceeding normal body weight (Overweight) is a cause of increased triglyceride levels. High triglyceride levels (hypertriglyceridemia) are a risk for coronary heart disease and diabetes mellitus. Efforts that can be made to reduce hypertriglyceridemia is to reduce the number of meals with the shof diet (sixteen hours of fasting). During fasting triglycerides will be mobilized to produce energy or synthesized into glucose. The aim of this study was to determine the effect of the shof diet on reducing triglyceride levels in overweight adolescents. The research design used the Pre-Experiment One Group Pretest-Postest Design with a population of all female students of the Faculty of Health Sciences who experienced overwight as much as 25. The number of samples was 20 with a sampling technique using purposive sampling. The research instrument uses an observation sheet. Data were analyzed using the Wilcoxon test with a P value ≤ α (α = 0.05). The results showed that the value of P = 0.646, which means that there was no effect of the shof diet on reducing triglyceride levels. However, in terms of quantity, there was a decrease in triglyceride levels in most of the respondents. The shof diet can reduce triglyceride levels by controlling food consumption during the fasting window.